Diagnostic accuracy and practice effects in the National Alzheimer's Coordinating Center Uniform Data Set neuropsychological battery. Issue 6 (24th March 2014) - Mathews, Melissa; Abner, Erin; Kryscio, Richard; Jicha, Gregory; Cooper, Gregory; Smith, Charles; Caban‐Holt, Allison; Schmitt, Frederick A.
Abstract: Introduction: The Uniform Data Set (UDS) neuropsychological battery is frequently used in clinical studies. However, practice effects, effectiveness as a measure of global cognitive functioning, and detection of mild cognitive impairment have not been examined. Methods: A normative total score for the UDS has been developed. Linear discriminant analysis determined classification accuracy in identifying cognitively normal and impaired groups. Practice effects were examined in cognitively normal and cognitively impaired groups. Results: The total score differentiates between cognitively normal participants and those with dementia, but does not accurately identify individuals with mild cognitive impairment (MCI). Mean total scores for test‐exposed participants were significantly higher than test‐naive participants in both the normal and MCI groups and were higher, but not significantly so, in the dementia group. Conclusion: The total score's classification accuracy discriminates between cognitively normal versus participants who have dementia. The total score appears subject to practice effects.